ANALYTICAL STUDY ON SECURITY AND ATTACKS CONCERNING WORMHOLE DETECTION IN STATIC WIRELESS SENSOR NETWORKS - Jagathese G Chelladurai,Dr. Mona Dwivedi (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2025)
Sensor nodes, when organized to build a WSN working below the switch of a central specialist, Improper position, are skilled of displaying fascinating applications due to their potential to be distributed widely in hostile and pervasive contexts. However, for the same reason, security is now a top concern for these networks. WSNs are susceptible to a variety of internal and external attacks due to their lack of tamper-proof packaging, limited processing power, memory capacity, and battery life. Because of their widespread use, WSNs are particularly susceptible to a variety of security risks. A denial-of-service attack is the most frequent and dangerous enemy to WSNs (DOS). Wormhole assault is another one of the several attack strategies. In order to achieve optimal network performance, a static clustering approach is suggested in this research. To assist in determining the initial energy allocation of these cluster heads and nodes, an energy model of this technique is offered. Finally, a simulation is shown to demonstrate how energy allocation is made to significantly lengthen network lifespan.